Effect of curcumin on the genotoxicity induced by alkylating agents - İbrahim Hakkı Ciğerci (Frontiers in Genetics, 2015)
The protection of the structure of DNA is extremly important to transfer genetic information from generation to generation. DNA damage due to genotoxic ess is an important type of stress which organisms are exposed during their life. The factors that cause DNA damage can be endogenous and exogenous. Among exogenous sources, alkylating agents comes first to cause DNA damage. Alkylating exogenous agents are capable of adding bases to ethyl or methyl groups. The direct-acting alkylating agent methyl methanesulfonate (MMS), is covalently linked to DNA and cause DNA damage, creating an indirect effect of the alkylating agent. cyclophosphamide (CP) causes the DNA damage by changing the function of cellular proteins. Both substances have been shown to induce gene mutations in prokaryotes and eukaryotes, chromosome effects, unscheduled DNA synthesis and sister chromatid exchange. Furthermore, cessation of cell growth arrest and DNA damage causing changes in gene expression have been observed by the stress due to alkylating agents exposure. In this study, the effects of curcumin on MMS and CP treated mice were investigated. Alkaline comet assay was used to detect DNA damage. Curcumin reduced the DNA damage, occurred by both MMS and CP induction. We could state that curcumin, a phenolic compound shows protective effects before the damage. In brief, curcumin has both antioxidant and antigenotoxic effects.